Exploring the Use of Selection, Optimization, and Compensation Strategies Beyond the Individual Level in a Workplace Context – A Qualitative Case Study - Karlsen, Iben Louise; Borg, Vilhelm; Meng, Annette (Frontiers in Psychology, 2022)
Due to aging populations and the prolonging of working lives, the number of senior workers will increase. Therefore, this study investigates the use of SOC strategies (Selection, Optimization, and Compensation) across organizational levels as a means for senior workers to maintain workability and age successfully at work. The need to expand the perspective of the SOC model beyond the individual level, when applied to a work context, has been emphasized theoretically in the literature, nevertheless, SOC strategies have so far only been examined at the individual level. This study is the first to explore SOC strategies at the organizational, leadership, and group level. We focus on senior employees and the SOC strategies they use to balance out demands and limited resources. Based on 23 semi-structured interviews with senior employees and immediate managers at two hospitals (nurses), and two dairies (skilled/unskilled workers), we explore which specific SOC strategies are used at each level and reflect on the applicability of broadening the perspective of the SOC model when applying it to a work context. Based on the empirical findings and the discussion of the empirical exploration of SOC strategies beyond the individual level, we argue that it is advantageous to further pursue this line of inquiry and include the group, leadership, and organizational level when applying the SOC model in a work setting.